2022
DOI: 10.3390/ijms23063232
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Proteostasis Decline and Protein Aggregation during Brain and Skeletal Muscle Aging

Abstract: Aging can be defined as the progressive deterioration of cellular, tissue, and organismal function over time. Alterations in protein homeostasis, also known as proteostasis, are a hallmark of aging that lead to proteome imbalances and protein aggregation, phenomena that also occur in age-related diseases. Among the various proteostasis regulators, microRNAs (miRNAs) have been reported to play important roles in the post-transcriptional control of genes involved in maintaining proteostasis during the lifespan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 105 publications
(172 reference statements)
0
4
0
Order By: Relevance
“…The role of MiRNAs in the proteostasis regulation such as translation, folding, and degradation has been reported recently. 72 A previous study found that miR-425 interacts with heat shock protein B8 (HSPB8) and promotes tau phosphorylation in HEK293/tau cells which is related to senescence-associated Alzheimer's disease. 73 Furthermore, organelle stress responses like ER stress contribute to the maintenance of proteostasis.…”
Section: Mirna Regulated Proteostasismentioning
confidence: 99%
“…The role of MiRNAs in the proteostasis regulation such as translation, folding, and degradation has been reported recently. 72 A previous study found that miR-425 interacts with heat shock protein B8 (HSPB8) and promotes tau phosphorylation in HEK293/tau cells which is related to senescence-associated Alzheimer's disease. 73 Furthermore, organelle stress responses like ER stress contribute to the maintenance of proteostasis.…”
Section: Mirna Regulated Proteostasismentioning
confidence: 99%
“…Recent publications have critically examined the diverse and multi-factorial aspects of aging and sarcopenia, including senescence-related changes linked to abnormal metabolic pathways [364], mitochondrial dysfunctions [365][366][367][368][369][370][371], the role of reactive oxygen species and disrupted redox signaling [372][373][374][375], abnormal calcium handling [376], functional changes in neuromuscular transmission [377], altered myokine and myomitokine signaling [369,378], the role of miRNAs in the decline of proteostasis [379,380], anabolic resistance and impaired muscle protein metabolism [381][382][383], adipocyte crosstalk in aged skeletal muscle and sarcopenic obesity [384,385], immune system alterations, chronic inflammation and immune-metabolic dysfunction associated with oxidative stress [33,366,[386][387][388], the role of telomere length during aged fiber regeneration [389], the interplay between sarcopenia, frailty and cognitive impairments in the elderly [390], cardio-sarcopenia syndrome [337] and the influence of nutrition on the aging phenotype [391]. The finding that the satellite cell pool is preferentially affected in fast type II fibers in the elderly [392] has established the idea that stem cell exhaustion is majorly involved in sarcopenia and possibly even facilitates age-associated fast-to-slow transitions [393].…”
Section: Pathobiological Hallmarks Of Sarcopenia Of Old Agementioning
confidence: 99%
“…In humans, 60% of protein-coding genes are regulated by miRNAs [17]. Numerous studies have shown that miRNAs play an important role in regulating aging processes, such as cognitive decline, inflammation, and neurodegenerative diseases, in mouse brains [18][19][20]. Li et al [21] analyzed miRNA expression datasets from human prefrontal cortex obtained from individuals aged 2 days to 98 years and proposed that age-related miRNAs play an important role during development and the aging process of the human brain.…”
Section: Introductionmentioning
confidence: 99%